CGIAR’s 2025-30 Portfolio Inception Reports: ISDC External Review Template - The Independent Science for Development Council (ISDC) (2025)
The Quality of Research for Development in the CGIAR Context (Qo4RD [2020]) is a framework that facilitates CGIAR System-wide agreement on the nature and assessment of the quality of science. It is the guiding pillar for ISDC’s criteria to assess science. The review template for the ISDC 2025 assessment of the Inception Reports uses 10 criteria that were adapted from previous reviews along with probing questions that crosscut among the four elements of QoR4D: relevance, scientific credibility, legitimacy, and effectiveness. The criteria will guide subject matter experts (SMEs) and ISDC members to reflect on and assess the Inceptions Reports.